2016
DOI: 10.3390/w8050206
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-Meteorological Drought Projections into the 21-st Century for Selected Polish Catchments

Abstract: Abstract:The nature of drought conditions is estimated using a range of indices describing different aspects of drought events. Three drought indices are evaluated, namely the Standardized Precipitation Index (SPI), Standardized Precipitation Evapotranspiration Index (SPEI) and Standardized Runoff Index (SRI), using observed hydroclimatic data and applying them to hydro-meteorological projections into the 21st century. The first two indices are evaluated using only meteorological variables and from this point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 46 publications
3
59
0
4
Order By: Relevance
“…Two recent drought studies listed in Table (Papadimitriou et al, ; Roudier et al, ) and two flood studies listed in Table (Alfieri et al, ; Roudier et al, ) fulfill the above criteria for comparison. Additionally, two relevant studies conducted specifically for Poland have been identified, one for low flows (Meresa, Osuch, & Romanowicz, ) and one for floods (Osuch, Lawrence, Meresa, Napiórkowski, & Romanowicz, ), and these are also discussed below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent drought studies listed in Table (Papadimitriou et al, ; Roudier et al, ) and two flood studies listed in Table (Alfieri et al, ; Roudier et al, ) fulfill the above criteria for comparison. Additionally, two relevant studies conducted specifically for Poland have been identified, one for low flows (Meresa, Osuch, & Romanowicz, ) and one for floods (Osuch, Lawrence, Meresa, Napiórkowski, & Romanowicz, ), and these are also discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…Our QL projections can also be compared to the Standardized Runoff Index (a runoff equivalent of the broadly used Standardized Precipitation Index) projections for 10 Polish catchments (of which nine lie in the VOB) for the near and FF under RCP 4.5 simulated by the Hydrologiska Byråns Vattenbalansavdelning (HBV) model forced by the bias‐corrected EURO‐CORDEX ensemble of seven climate models (Meresa et al, ). While in most of catchments, they showed consistently wetter conditions (i.e., decreased probability of drought recurrence, decreased drought severity) in agreement with our projections, in some catchments, the spread due to climate models was very high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study into the impact of climate change (precipitation and temperature patterns) on flows in Poland was conducted by Piniewski et al (2016Piniewski et al ( , 2017a Osuch et al (2016Osuch et al ( , 2017, Meresa et al (2016) and Romanowicz et al (2016). Most of these studies mainly focused on the prediction of frequency and severity of droughts and floods.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been published on the influence of climate changes on floods and droughts Romanowicz et al 2016;Meresa et al 2016;Kundzewicz et al 2017a). However, the picture of future changes is far from clear.…”
mentioning
confidence: 99%